Analysis of the Relationship between Organizational Culture, Job Satisfaction, and Work Motivation on Employee Productivity - Sugito Sugito (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze the influence of Organizational Culture, Work Motivation and Job Satisfaction on Employee Performance of East Java “Veteran” National Development University. The population in this study were all employees of the production section of East Java “Veteran” National Development University with 77 employees. The sample in this study was 77 respondents. Determination of the sample in this study using the census method. This research data analysis tool uses multiple linear regression. The results showed that organizational culture had a positive effect on employee performance. This is evidenced by the calculated t value greater than t table that is 2.587 > 1.667, with a significant value of 0,000 < 0.05 so that it is significant. Work motivation has a positive effect on employee performance. This is evidenced by the t value of 1.922 is greater than t table that is 1.667, with a significant value of 0.008 < 0.05 means significant. Job satisfaction has a positive effect on employee performance. This is evidenced by the t value of 1.955 greater t table that is 1.667, with a significant value of 0.004 < 0.05 means significant.